Frequent Multidrug-Resistant Acinetobacter baumannii Contamination of Gloves, Gowns, and Hands of Healthcare Workers - Morgan, Daniel J. (2010)
BACKGROUND: Multidrug-resistant (MDR) gram-negative bacilli are important nosocomial pathogens. OBJECTIVE: To determine the incidence of transmission of MDR Acinetobacter baumannii and Pseudomonas aeruginosa from patients to healthcare workers (HCWs) during routine patient care. DESIGN: Prospective cohort study. SETTING: Medical and surgical intensive care units. METHODS: We observed HCWs who entered the rooms of patients colonized with MDR A. baumannii or colonized with both MDR A. baumannii and MDR P. aeruginosa. We examined their hands before room entry, their disposable gloves and/or gowns upon completion of patient care, and their hands after removal of gloves and/or gowns and before hand hygiene. RESULTS: Sixty-five interactions occurred with patients colonized with MDR A. baumannii and 134 with patients colonized with both MDR A. baumannii and MDR P. aeruginosa. Of 199 interactions between HCWs and patients colonized with MDR A. baumannii, 77 (38.7% [95% confidence interval CI, 31.9%–45.5%]) resulted in HCW contamination of gloves and/or gowns, and 9 (4.5% [95% CI, 1.6%–7.4%]) resulted in contamination of HCW hands after glove removal before hand hygiene. Of 134 interactions with patients colonized with MDR P. aeruginosa, 11 (8.2% [95% CI, 3.6%–12.9%]) resulted in HCW contamination of gloves and/or gowns, and 1 resulted in HCW contamination of hands. Independent risk factors for contamination with MDR A. baumannii were manipulation of wound dressing (adjusted odds ratio [aOR], 25.9 [95% CI, 3.1–208.8]), manipulation of artificial airway (aOR, 2.1 [95% CI, 1.1–4.0]), time in room longer than 5 minutes (aOR, 4.3 [95% CI, 2.0–9.1]), being a physician or nurse practitioner (aOR, 7.4 [95% CI, 1.6–35.2]), and being a nurse (aOR, 2.3 [95% CI, 1.1–4.8]). CONCLUSIONS: Gowns, gloves, and unwashed hands of HCWs were frequently contaminated with MDR A. baumannii. MDR A. baumannii appears to be more easily transmitted than MDR P. aeruginosa and perhaps more easily transmitted than previously studied methicillin-resistant Staphylococcus aureus or vancomycin-resistant Enterococcus. This ease of transmission may help explain the emergence of MDR A. baumannii.